Effect of substitution of normal weight coarse aggregate with oil-palm-boiler clinker on properties of concrete - Lee, Jin Chai; Payam Shafigh,; Hilmi Mahmud,; Muhammad Aslam, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Oil-palm-boiler clinker (OPBC) is an agricultural solid waste sourced from the palm oil industry in tropical regions. This study investigates the use of OPBC as coarse aggregate instead of conventional coarse aggregates to produce a greener concrete, which will help in implementing sustainable construction practices by reducing the usage of raw materials. For this purpose, normal weight coarse aggregates was substituted with dry OPBC aggregates up to 75% (by volume) in a high strength normal weight concrete. The effectiveness of this substitution on the properties of the concrete such as workability, density, compressive strength, splitting tensile strength and modulus of elasticity was studied. The slump test results showed that using OPBC in dry condition reduced the workability of the concrete and therefore can be used up to 50% of the total volume of coarse aggregate. Concrete containing 50% OPBC can be considered as semi-lightweight concrete with high strength. Using OPBC in concrete reduced the splitting tensile strength and modulus of elasticity, however, the reduction was not significant.